1988
DOI: 10.1136/jnnp.51.7.909
|View full text |Cite
|
Sign up to set email alerts
|

Does a "moderate" alcohol intake damage the brain?

Abstract: SUMMARY A range of volumetric and neurochemical analyses were carried out on the brains of 14 "moderate" drinkers. These data were compared with previous studies from controls and alcoholics. Volumetric measurements consistently suggest a loss of cerebral tissue although the differences were not statistically significant. Changes in the lipid and water content of the white matter were noted and the significance of these changes in relation to the pathogenesis of reversible brain shrinkage caused by alcohol abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0
4

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 23 publications
1
20
0
4
Order By: Relevance
“…Although the difference in various brain measures between the moderate drinkers and the control group was not statistically significant, this autopsy study revealed a consistent trend in the measures suggesting loss of cerebral tissue, as evidenced by reduced cerebral weight, increased ventricular volume and pericerebral space, the main loss being in white matter. 40 White matter is composed of approximately 70% water, 20% lipids and 10% protein. 41 and most of the latter two elements is combined to form membranes (myelin in particular).…”
Section: Pathologymentioning
confidence: 99%
“…Although the difference in various brain measures between the moderate drinkers and the control group was not statistically significant, this autopsy study revealed a consistent trend in the measures suggesting loss of cerebral tissue, as evidenced by reduced cerebral weight, increased ventricular volume and pericerebral space, the main loss being in white matter. 40 White matter is composed of approximately 70% water, 20% lipids and 10% protein. 41 and most of the latter two elements is combined to form membranes (myelin in particular).…”
Section: Pathologymentioning
confidence: 99%
“…Buscando avaliar o impacto do consumo "moderado" de álcool no cérebro, pesquisadores avaliaram medidas cerebrais como peso cerebral, espaço pericerebral e volume ventricular de bebedores moderados (30-80g de álcool/dia), alcoolistas (mais de 80g de álcool/dia), alcoolistas com cirrose, alcoolistas com encefalopatia de Wernicke e grupo-controle de abstêmios ou bebedores de até 20g álcool/dia. Embora não tenham encontrado diferença estatisticamente significativa entre as medidas cerebrais de bebedores "moderados" e grupo-controle, há uma tendência sugerindo perda de tecido cerebral, com peso cerebral reduzido, aumento do volume ventricular e do espaço pericerebral, sendo maior a perda de substância branca 17 . A substância branca é formada de aproximadamente 70% de água, 20% de lipídios e 10% de proteína 39 , sendo que a maioria destes dois últimos elementos está combinada na forma de membranas (mielina particularmente).…”
Section: Patologiaunclassified
“…Lesões desmielinizantes mostram aumento do conteúdo de água e decrésci-mo no conteúdo de lipídio, invertendo o processo que ocorre durante a maturação cerebral 12 . O padrão de alteração dos conteúdos de água e de lipídio da substância branca cerebral de pacientes alcoolistas é semelhante ao padrão de alteração do envelhecimento e ao padrão de lesões desmielinizantes observados no estudo supracitado 17 . Ratos expostos ao álcool por cinco meses apresentaram uma redução significativa das ramificações dendríticas no hipocampo, que reverteu após dois meses de abstinência 37 .…”
Section: Patologiaunclassified
See 1 more Smart Citation
“…However, with consumption of 300 g of ethanol per day, brain volume may shrink over 20%. 7 In alcoholics, brain shrinkage is part of the postalcohol remorse; but in all others, drinking a couple of drinks per day may lead to a lifelong hangover. …”
mentioning
confidence: 99%